ENDRIN INDUCED HEPATIC INJURY IN CHANNA PUNCIATUS (HAM.) - Sastry, K V; Sharma, S K (Indian Journal of Fisheries, 2011)
Ths effffect of a sublethal concentration (0.01 mg/1) of endrin on the histological chrnges in the liver of a ^^leost fish, Channa punctatus (Ham.) has been studied. The degenerative changes included hype^rtrophy of hepEtic cells and their nuclei, liver cord disarray, vacuolation of cytoplasm and necrosis. In some cells, the cell membrane was ruptured. The centrolobular area was highly necrosed. The liver on the whole showed distorted appearance